Chronic sleep restriction during juvenility alters hedonic and anxiety-like behaviours in a sex-dependent fashion in adolescent Wistar rats - Barreto, Anna Carolina Muniz; Oliveira, Julia Naomi Sakamoto; Suchecki, Deborah (Frontiers in Neuroscience, 2024)
Chronic reduction of sleep time in children and adolescents has been related to increased incidence of anxiety and depression. In rats, protocols of protracted sleep deprivation or chronic sleep restriction (CSR) are considered a stressor. In previous studies we showed that post-weaning CSR in male rats induces anxiety-like behaviour and changes in neurotransmission in emotion-related brain areas. In the present study we examined whether the effects of this adversity are sexdependent. Twenty-two litters, containing 4 males and 4 females were distributed into control (CTL) and CSR groups. CSR began on postnatal day (PND) 21 and lasted for 21 days; each day the animals were placed onto small platforms immersed in water for 18 h and were allowed to sleep freely in their home-cages for the remaining 6 h. Throughout the CSR, all animals underwent the sucrose splash test once/week to assess their self-care and hedonic behaviours. Body weight was measured on PNDs 21 and 42. At the end of CSR period, the adolescents were allowed to sleep freely for 2 days, after which, behavioural tests began. Within each litter, one male and one female (pair) were not tested and provided blood and brain for determination of basal corticosterone (CORT) levels and hippocampal BDNF. One pair was tested in the sucrose preference test (SPT), one pair on the elevated plus maze (EPM) and one pair in the forced swim test (FST). CORT was measured after all conditions. CSR impaired self-care behaviour and body weight gain in males and females and increased relative adrenal weight only in males. There were no changes in sucrose intake in the SPT; CSR females displayed less immobility in the FST and CSR males displayed more anxiety-like behaviour in the EPM. CORT levels were similar between CTL and CSR males, whilst lower in CSR females than CTL ones in all experimental conditions. No changes in BDNF levels were detected in the dorsal hippocampus of CSR rats. The results indicate that CSR impaired self-care behaviour in both sexes, but only males displayed anxiety-like behaviour, whilst sleep recovery in females appeared to normalise their behaviour.